In the Blink of an Eye: Neural Responses Elicited to Viewing the Eye Blinks of Another Individual - Brefczynski-Lewis, Julie A.; Berrebi, Michael; McNeely, Marie; Prostko, Amy; Puce, Aina (Frontiers in Human Neuroscience, 2011)
Facial movements have the potential to be powerful social signals. Previous studies have shown that eye gaze changes and simple mouth movements can elicit robust neural responses, which can be altered as a function of potential social significance. Eye blinks are frequent events and are usually not deliberately communicative, yet blink rate is known to influence social perception. Here, we studied event-related potentials (ERPs) elicited to observing non-task relevant blinks, eye closure and eye gaze changes in a centrally presented natural face stimulus. Our original hypothesis (H1) that blinks would produce robust ERPs (N170 and later ERP components) was sustained, suggesting that the brain may register and process all types of eye movement for potential social relevance. We also predicted an amplitude gradient for ERPs as a function of gaze change, relative to eye closure and then blinks (H2). H2 was only partly sustained: large temporo-occipital N170s to all eye change conditions were observed and did not significantly differ between blinks and other conditions. However, blinks elicited late ERPs that, although robust, were significantly smaller relative to gaze conditions. Our data indicate that small and task-irrelevant facial movements such as blinks are measurably registered by the observer’s brain. This finding is suggestive of the potential social significance of blinks which, in turn, has implications for the study of social cognition and use of real-lfe social scenarios.